Blood pressure, ethnic group, and salt intake in Belize. Issue 1 (March 1983) - Simmons, D
Abstract : A total of 1316 individuals were studied in seven villages in Belize, Central America. This represented 92% of the area population aged over 18. Generally, they were members of three ethnic groups--Maya, Spanish, and Creole. The systolic and diastolic IV and V blood pressures were recorded using standardised procedure. Significant differences in blood pressure, weight, and obesity were found between ethnic groups in both sexes, Creoles having higher means than the other groups. Significant relationships with blood pressure were found with obesity, age, and number of children. An early morning urine specimen was obtained from a random 50% of the men, and only in Creoles was there an association between raised blood pressure and sodium/potassium urinary excretion ratio.